Eksistensi, Regulasi, dan Fungsi Meunasah Sebagai Lembaga Pendidikan Islam di Aceh - Mahmazar, Mahmazar; Mulyadi; Miswari (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2023)
This article aims to analyze the existence, regulation, and function of the meunasah as a center for religious and cultural activities in society, including Islamic religious education institutions. This study uses a qualitative approach. Data were collected from literature related to research objects and field data through observation, interviews and documentation. The research findings show that the existence of meunasah is not only a cultural heritage which is the center of community activities, but also an institution that has a clear legal standing. The clarity of the legal status of the meunasah as a center for various community activities departs from the special status of Aceh as an autonomous region. The existence of meunasah is a local translation for educational activities in the Muslim world community, especially from the Middle East, namely madrasas. The word meunasah is also an adaptation of the tongue of the Acehnese people from the word madrasa. By regulation, various qanuns have been stipulated regarding the existence of the meunasah. Among the important functions of the meunasah is the implementation of Islamic religious education. The existence of religious education institutions in meunasah in agrarian societies is part of the hierarchy of the traditional education system. Meanwhile in urban areas, the existence of meunasah as educational institutions is a center of recitation such as center for religious studies and center for the study of the Qur’an.